2019
DOI: 10.1002/jcb.28340
|View full text |Cite
|
Sign up to set email alerts
|

HOX transcript antisense RNA is elevated in gastric carcinogenesis and regulated by the NF‐κB pathway

Abstract: The expression pattern of HOX transcript antisense RNA (HOTAIR) in the progression of gastric cancer and the regulation of its expression are still unclear. In the current study, HOTAIR expressions in gastric tissues collected from patients with superficial gastritis, atrophic gastritis, atypical hyperplasia, and gastric cancer as well as normal controls was quantitatively examined. The results showed that the expression of HOTAIR was higher in gastric cancer than in normal tissues, but reached the highest lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…To better characterize the HOTAIR role in GC carcinogenesis, we analyzed HOTAIR expression in preneoplastic changes. Zhang et al reported on initial HOTAIR expression analysis in gastric tissues, showing the highest expression in AG ( 12 ). In our results, we observed no expression of HOTAIR in controls, but it was upregulated in patients with CNAG and AG and/or patients with IM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better characterize the HOTAIR role in GC carcinogenesis, we analyzed HOTAIR expression in preneoplastic changes. Zhang et al reported on initial HOTAIR expression analysis in gastric tissues, showing the highest expression in AG ( 12 ). In our results, we observed no expression of HOTAIR in controls, but it was upregulated in patients with CNAG and AG and/or patients with IM.…”
Section: Discussionmentioning
confidence: 99%
“…Various lncRNAs are highly expressed in GC tissues and have been evaluated as GC biomarkers ( 6 , 8 ). LncRNA Hox transcript antisense intergenic RNA (HOTAIR) is upregulated in GC tissue ( 11 , 12 ). HOTAIR targets miR-34a and activates the PI3K/AKT pathway and leads to tumor progression by inhibiting apoptosis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB contributes to the regulation of the invasive properties of human gastric carcinoma cells by stimulating the production of, e.g., MMP-9 in response to IL-1β or MMP-2 and MMP-12 in response to TNF-CXCL1/CXCL2-S100A8/9 activation [ 143 , 144 , 145 ]. In atrophic gastritis and GC tissue, RelA has been suggested to potentiate the expression of the long-noncoding RNA HOX transcript antisense RNA (HOTAIR), which promotes cell motility and invasion through targeting Wingless int 1 (Wnt)/β-catenin and poly-r(C)-binding protein (PCBP) [ 146 ]. In addition, NF-κB is involved in the up-regulation of Snail1, which leads to E-cadherin reduction in GC tissue [ 114 ].…”
Section: Nf-κb-regulated Genes and Their Relevance For Gastric Cancer Developmentmentioning
confidence: 99%
“…In considering how high glucose may upregulate HOTAIR, we were cognisant of work reporting a role for the p65 subunit of NF-κB in regulating the expression of human HOTAIR [33,34]. We performed in silico analysis of the mouse Hotair promoter and identified three potential binding sites for NF-κB (ESM Fig.…”
Section: Exposure To High Glucose Increases Hotair Expression By Mousmentioning
confidence: 99%